Age Differences in Nonhedonic Entertainment Experiences. (8th January 2014) - Hofer, Matthias; Allemand, Mathias; Martin, Mike
<x xml:space="preserve">Abstract</x> This article examines age differences in nonhedonic (eudaimonic) entertainment experiences. Results of an experimental study comparing younger adults aged 18 to 28 years (n = 84) with older adults aged 62 to 87 years (n = 65) who watched either a sad or a happy version of a meaningful film show that generally, older viewers reported higher levels of eudaimonic entertainment than younger participants. Furthermore, among older participants, eudaimonic entertainment experiences during the film were associated with positive affect and mixed emotions. This study further develops our understanding of nonhedonic entertainment experiences. Implications for other research areas are discussed.